2014
DOI: 10.3168/jds.2013-7095
|View full text |Cite
|
Sign up to set email alerts
|

Amylase addition increases starch ruminal digestion in first-lactation cows fed high and low starch diets

Abstract: The objective of this study was to evaluate the effect of an exogenous amylase preparation on digestion of low- and high-starch diets in dairy cattle. Rumen and total-tract nutrient digestibility were measured in a 4×4 Latin square design with 28-d periods using 4 first-lactation cows cannulated at the rumen and duodenum. Corn silage-based diets had 20 or 30% starch, attained by changing the composition of concentrate, with or without addition of an exogenous amylase preparation. Effects of the enzyme additive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
62
4
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 31 publications
17
62
4
12
Order By: Relevance
“…Xylanolytic enzyme group includes endo-$-1,4-xylanase (1,4-$-D xylan xylanohydrolase, EC 3.2.1.8), which attack the main chain of xylans and $-D-xylosidase (1,4-$-xylan xylanohydrolase, EC 3.2.1.37), which hydrolyze xylooligosaccharides into D-xylose, in addition to a variety of debranching enzymes that is, "-L-arabino-furanosidases, "-glucuronidases and acetyl esterases (Kamble and Jadhav, 2012). Though researches hypothesized that the digestion of starch and protein is not limited within rumen, recent researches conducted with enzyme supplementation with amylolytic activity (Noziere et al, 2014;Klingerman et al, 2009;Gencoglu et al, 2010) and proteolytic activity (Eun and Beauchemin, 2005;Vera et al, 2012) have examined the potential of these enzymes to improve animal performance. Amylase has been divided into three sub classes as ", $ and ( amylase based on the bonding type (Gurung et al, 2013).…”
Section: Types Sources and Extraction Of Enzymesmentioning
confidence: 99%
“…Xylanolytic enzyme group includes endo-$-1,4-xylanase (1,4-$-D xylan xylanohydrolase, EC 3.2.1.8), which attack the main chain of xylans and $-D-xylosidase (1,4-$-xylan xylanohydrolase, EC 3.2.1.37), which hydrolyze xylooligosaccharides into D-xylose, in addition to a variety of debranching enzymes that is, "-L-arabino-furanosidases, "-glucuronidases and acetyl esterases (Kamble and Jadhav, 2012). Though researches hypothesized that the digestion of starch and protein is not limited within rumen, recent researches conducted with enzyme supplementation with amylolytic activity (Noziere et al, 2014;Klingerman et al, 2009;Gencoglu et al, 2010) and proteolytic activity (Eun and Beauchemin, 2005;Vera et al, 2012) have examined the potential of these enzymes to improve animal performance. Amylase has been divided into three sub classes as ", $ and ( amylase based on the bonding type (Gurung et al, 2013).…”
Section: Types Sources and Extraction Of Enzymesmentioning
confidence: 99%
“…Nozière et al (2014) did not report any positive effects on animal performance with enzyme supplementation higher than doses in current experiment, even though the inclusion of exogenous amylolytic enzymes increased by 8% the degradability of starch in the rumen without any increase in starch digestibility in the entire digestive tract. In an experiment with beef cattle in feedlot with the inclusion of 580 amylolytic units of amylase per kg of dry matter of the diet, J. M. Tricarico et al (2007) registered an increase in voluntary intake of DM and weight gain in the first 28 days in feedlot (14%).…”
Section: Resultsmentioning
confidence: 90%
“…This hydrolysis occurs through the cleavage of the α-1.4 and α-1.6 bonds of the starch granules (Tricarico, Johnston, & Dawson, 2008). This effect of amylase is due to the greater hydrolysis of starch (Nozière et al, 2014) providing substrates for the multiplication of other microbial species, mainly fibrolytic micro-organisms (Mccarthy, Engstrom, Azem, & Gressley, 2013), a process defined as cross-feeding among rumen micro-organisms (Russell, 1985) that can improve fibre digestibility by increase in fibre digestion rate as shown in our study. Likewise, Gallo et al (2016) observed that amylase decreased lag time and increased rate and amount of gas production.…”
Section: Fermentation Kinetics and In Vitro Dry Matter Digestibilitymentioning
confidence: 99%
“…The use of exogenous amylase increases rumen starch degradation (Nozière, Steinberg, Silberberg, & Morgavi, 2014;Vargas-Rodriguez, Engstrom, Azem, & Bradford, 2014). However, responses to exogenous amylase are influenced by the inclusion level and particle size of maize silage (Gallo, Giuberti, Duval, Moschini, & Masoero, 2016) and these studies were made all in temperate conditions using basically dent-type maize hybrids.…”
Section: Introductionmentioning
confidence: 99%